2011
DOI: 10.1016/j.cmet.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Estrogen-Related Receptor Directs a Metabolic Switch that Supports Developmental Growth

Abstract: Summary Metabolism must be coordinated with development to provide the appropriate energetic needs for each stage in the life cycle. Little is know, however, about how this temporal control is achieved. Here we show that the Drosophila ortholog of the Estrogen-Related Receptor (ERR) family of nuclear receptors directs a critical metabolic transition during development. dERR mutants die as larvae with low ATP levels and elevated levels of circulating sugars. The expression of active dERR protein in mid-embryoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
203
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(222 citation statements)
references
References 48 publications
12
203
1
Order By: Relevance
“…Ultimately, a key result of ERRα expression and activity appears to be to promote stability or translation of glycolytic proteins and the flux of pyruvate into acetyl-CoA and the TCA cycle, possibly through regulation of DLAT and PDK1 expression. An inability to properly direct glucose to mitochondrial metabolism would lead to decreased lipid synthesis and cell growth, similar to what has been described in ERR-deficient Drosophila (22).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Ultimately, a key result of ERRα expression and activity appears to be to promote stability or translation of glycolytic proteins and the flux of pyruvate into acetyl-CoA and the TCA cycle, possibly through regulation of DLAT and PDK1 expression. An inability to properly direct glucose to mitochondrial metabolism would lead to decreased lipid synthesis and cell growth, similar to what has been described in ERR-deficient Drosophila (22).…”
Section: Resultsmentioning
confidence: 95%
“…The orphan nuclear hormone receptor, estrogen-related receptor-α (ERRα), is associated with poor prognosis (16,17) and tumor growth in breast cancer (18,19). ERRα is also known to regulate cell metabolism (20,21) and Drosophila ERR can promote gene expression to drive carbohydrate metabolism associated with proliferating cells in larval development (22). In immunity, ERRα −/− mice exhibit increased susceptibility to Listeria monocytogenes infection (23).…”
mentioning
confidence: 99%
“…A ChIP-Chip analysis 30 and a recent ChIP-seq study of mouse liver 29 demonstrated that ERRa is involved in the regulation of genes involved in energy metabolism, including glycolysis, the TCA cycle, oxidative phosphorylation and lipid metabolism. Moreover, Drosophila ERR was also shown to regulate glycolytic gene expression in mid-embryogenesis 46 . Accordingly, with a focus on glycolytic genes, we compared the ChIP-seq data sets for Ad4BP/SF-1 and ERRa.…”
Section: Discussionmentioning
confidence: 99%
“…The production of VMH-specific Ad4BP/SF-1-deficient mice that could survive postnatally allowed for experiments that linked the loss of Ad4BP/SF-1 with high-fat diet-induced obesity and impaired thermogenesis 46 . Although the precise mechanisms underlying these connections remain to be delineated, it might be noteworthy that the expression of genes participating in metabolic regulation, for example, the leptin receptor, was downregulated in VMH-specific Ad4BP/SF-1 null animals.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating and stored carbohydrate levels were measured via a modified method from the original (Tennessen et al 2011) (see Supplementary Materials and methods). Lipid measurements were performed as described previously (Williams et al 2014b).…”
Section: Trehalose Glucose and Lipid Analysismentioning
confidence: 99%